A Concise Review on Nano‐emulsion Formation by the Phase Inversion Composition (PIC) Method. Issue 4 (14th April 2020) - Feng, Jin; Rodríguez‐Abreu, Carlos; Esquena, Jordi; Solans, Conxita
Abstract: Nano‐emulsion formation by the phase inversion composition method is reviewed. The relationship between phase behavior and nano‐emulsion formation is revised with emphasis on the key role of phase transitions involving changes in the sign of the curvature of the surfactant layer (inversion) via zero‐average‐curvature structures such as bicontinuous microemulsions or lamellar liquid crystalline phases. The different low‐energy methods that can be involved in a nano‐emulsification process at constant temperature are also discussed. Abstract :